Urban prototypes: the importance of the small in changing the big - Mhlongo, Siphephelo Njomane Nqaba (My University, 2017)
The end of apartheid signalled the need to reinvent and re-configure South African cites not just spatially but economically as well, to be more inclusive of the people it once marginalized and excluded. South Africa’s urban identity is intrinsically intertwined with the history of apartheid to the point where it is impossible to have the one without the other. Johannesburg much like all the other cities in South Africa is and was an Apartheid project; the city was a tool used to perpetuate and enforce a system of economic exclusion which later developed into social and cultural segregation. Despite its nearly complete re-population after 1994, the city today, as dynamic and vibrant as it is, still poses remnants of the apartheid era. The people who had not been allowed into the city have become its primary residents, yet not its owners. And because the city was never designed for them, they have had to make, re-make and reconfigure the city for themselves. Through this process of making, re-making and re-configuring innovative solutions to everyday problems are tried tested and developed to integrate the urban African into the city. The changing demographics manifested growth through informal infill to create the Johannesburg we know today. It is by the process of negotiation between the formal and the informal economy that Johannesburg assumes its identity. The resilience of the informal economy could be attributed to the social networks that govern its relationships. The combination of social networks and the process of re-making the city suggest the informal as a strategy for urban regeneration that heals the city in its entirety by intervening in sensitive points in the urban fabric. This thesis investigates the shifting role of the informal in, the need for a change in approach when dealing with the informal and looks at the informal as a skill and form of knowledge.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa; Urban renewal--South Africa; Urbanization--South Africa